Carcerality, theatre, rights. Issue 3 (3rd July 2021) - Woodland, Sarah; Hazou, Rand
ABSTRACT: Threatened with ever-increasing levels of surveillance and confinement, this special issue attempts to extend the discussion of Prison Theatre to consider 'carcerality' as a pervasive neoliberal strategy. The issue aims to steer the discussion away from considerations of utility and the aesthetics of redemption, towards understandings of the arts in carceral spaces as a fundamental human right. What role can theatre and performance play in highlighting the rights of those experiencing state-sponsored control, confinement and exclusion? And what role can theatre and performance play in challenging the exclusionary structures of carcerality by enhancing freedoms, liberty and inclusion?